2017
DOI: 10.1287/mnsc.2016.2502
|View full text |Cite
|
Sign up to set email alerts
|

Platform Integration and Demand Spillovers in Complementary Markets: Evidence from Facebook’s Integration of Instagram

Abstract: Social media platform owners often choose to provide tighter integration with their own complementary applications (i.e., first-party applications) as compared to that with other complementary third-party applications. We study the impact of such integration on consumer demand for first-party applications and competing third-party applications by exploring Facebook’s integration of Instagram, an application in its photo-sharing application ecosystem. We find that consumers obtain additional value from Instagra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
94
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(100 citation statements)
references
References 59 publications
1
94
0
Order By: Relevance
“…Despite the policy and managerial implications of the tension between platform owners and complementors, the related literature is still nascent, with only a few empirical papers on the drivers and consequences of value appropriation by platform owners (e.g., Edelman & Lai, ; Gawer & Cusumano, ; Gawer & Henderson, ; Li & Agarwal, ; Zhu & Liu, ) . One important but unexplored question is whether and how complementors adjust value‐creation and value‐capture strategies when the threat of platform‐owner entry increases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the policy and managerial implications of the tension between platform owners and complementors, the related literature is still nascent, with only a few empirical papers on the drivers and consequences of value appropriation by platform owners (e.g., Edelman & Lai, ; Gawer & Cusumano, ; Gawer & Henderson, ; Li & Agarwal, ; Zhu & Liu, ) . One important but unexplored question is whether and how complementors adjust value‐creation and value‐capture strategies when the threat of platform‐owner entry increases.…”
Section: Introductionmentioning
confidence: 99%
“…First, it adds to an emerging body of research on firm strategies in platform‐based markets (e.g., Cennamo & Santalo, , ; Claussen, Essling, & Kretschmer, ; Eisenmann, Parker, & Van Alstyne, ; Kretschmer & Claussen, ; McIntyre & Srinivasan, ; Panico & Cennamo, ; Parker & Van Alstyne, ; Rochet & Tirole, ; Zhang, Li, & Tong, ; Zhu & Iansiti, ). A small number of empirical studies concern platforms' boundary decisions and focus on the consequences of platform‐owner entry into complementary markets (e.g., Edelman & Lai, ; Li & Agarwal, ; Pierce, ; Wan & Wu, ; Zhu & Liu, ). Our study differs from existing studies in two important ways.…”
Section: Introductionmentioning
confidence: 99%
“…This contributes to the emerging, nascent literature on platform integration. While prior research has looked at user engagement in a 3D virtual world context (Frutiger et al 2014), user engagement on social media sites (Li and Agarwal 2016), and user content contribution behaviors in an online review context (Huang et al 2016), this study provides a pioneering experimental analysis of the economic value of social media integration, as measured by its impact on users' online shopping behaviors in e-commerce. Furthermore, this study contributes to literature on social learning (Banerjee 1992, Chen et al 2011) by providing evidence of both a positive learning effect and a negative learning effect in an e-commerce context.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Frutiger et al (2014) studied the social login feature in the context of a 3D virtual world platform and found that use of a social login significantly reduces the registration of new users, the engagement of existing users with the 3D virtual world, and the number of friends the existing users add. In another study, Li and Agarwal (2016) found that the growth of Instagram's user base had a positive spillover effect on large third-party applications, but a negative spillover effect on small third-party applications in Facebook's photo-sharing ecosystem. Additionally, Huang et al (2016) investigated users' content contribution behavior after two online review platforms, TripAdvisor.com and Yelp.com, integrated successfully with Facebook.…”
Section: Social Media Integrationmentioning
confidence: 99%
See 1 more Smart Citation